Architecture of pure geometry: Dwellings houses of architects Stevan i Milena Tešić - Janakova-Grujić Mare (Arhitektura i Urbanizam, 2009)
Article describes part of work of Serbian's architects Stevan Tešić and Milena Veljković Tešić. The works have been designed and made in Italy from 2000 to 2008 and have been dedicated to dwellings houses. Following up developmental creative line, we can observe basic characteristics and particularity: urban sense, attitude to cultural and historical heritage and subject matter of works which is narrowly.